Analisis Upaya Guru dalam Meningkatkan Kemampuan Literasi dan Numerasi Peserta Didik di SD Negeri Gemah - Riyani, Siti Rosidah; Purnamasari, Veryliana (ISLAMIKA, 2024)
Literacy and numeracy education in Indonesia requires substantial attention from primary education through to higher education to support global economic progress. Although the 2013 Curriculum is designed to enhance literacy culture, Indonesia still faces significant challenges, including low literacy rates and a lack of understanding of the issue in various regions. This study seeks to investigate and examine the role of teachers in enhancing literacy and numeracy skills at SD Negeri Gemah, focusing on the teaching strategies employed and the challenges encountered. Employing a qualitative approach and case study design, this research includes detailed interviews, participant observations, and document analysis, involving six classroom teachers as participants. The study's findings reveal that educators at Gemah State Elementary School employ a range of literacy and numeracy teaching strategies, including shared reading, group discussions, digital media, and both Problem-Based Learning (PBL) and Project-Based Learning (PJBL) methods to improve numeracy skills.. The main challenges faced include the transition from kindergarten to elementary school, difficulties in reading and arithmetic, lack of student interest, and differences in students' abilities. Proposed solutions include collaboration with teachers of other subjects, the use of diverse learning media, parental support, and providing additional learning opportunities outside of classroom hours. The study concludes that diverse teaching approaches and comprehensive support are essential in improving students' literacy and numeracy skills. By implementing an integrated solution, it is hoped that SD Negeri Gemah can overcome existing challenges and better prepare students for higher education.